A facile strategy to synthesize graphitic carbon-encapsulated core-shell nanocomposites derived from CO2 as functional materials. (December 2020) - Yu, Rui; Deng, Bowen; Zheng, Kaiyuan; Wang, Xingyi; Du, Kaifa; Wang, Dihua
Abstract : A facile strategy to design graphitic carbon-encapsulated NiCo core-shell nanocomposites (NiCo@g-C) is achieved by a simple co-electrolysis process involving CO2 reduction. Carbon derived from the captured CO2 is uniformly deposited on the surface of as-prepared NiCo particle to form homogeneous coatings at a suitable processing condition. It is very interesting to reveal that the carbon coatings are in graphitic structures with an average thickness of ~70 nm due to the in-situ catalytic graphitization effect of reduced transition metal (Ni, Co). More interestingly, it is found that the as-formed graphite coatings can effectively inhibit the sintering between NiCo nucleis under a high operating temperature, resulting in the smaller particle size of NiCo@g-C than that of the obtained NiCo alloys without carbon coatings. Owing to the novel nanostructures, the NiCo@g-C shows excellent magnetic properties and enhanced hydrogen evolution reaction activity in comparison with bare NiCo alloys. This work gives a new clue to designing functional carbon-encapsulated metal/alloy composites with unique nanostructures at a relatively mild condition. Highlights: The affordable scale-up production of functional composites was achieved. The uniform graphite coatings of composites were derived from CO2 . The formation mechanism of composites was proposed. The composites showed smaller particle scale due to barrier effect of graphite coatings. The composites exhibited excellent magnetic properties and enhanced HER performance.